Influence of co-morbidity on long-term quality of life after oesophagectomy for cancer. (29th January 2014) - Djärv, T; Derogar, M; Lagergren, P
Abstract: Background: The extent to which co-morbidities affect recovery of health-related quality of life (HRQoL) in long-term survivors of oesophageal cancer surgery is poorly understood. Methods: This was a prospective, population-based, nationwide Swedish cohort study of patients who underwent surgery for oesophageal cancer between 2001 and 2005, and were alive 5 years after operation. The European Organization for Research and Treatment of Cancer QLQ-C30 and the QLQ-OES18 questionnaires were used to assess HRQoL up to 5 years after surgery. Eight aspects from the questionnaires were selected. Matched reference values from the Swedish general population were used as a proxy for HRQoL before presentation of the cancer. Adjusted multivariable linear mixed-effect models were used to assess mean score differences (MDs) of each HRQoL aspect in patients with or without co-morbidities. Results: Of 616 patients who underwent surgery, 153 (24·8 per cent) survived 5 years, of whom 141 (92·2 per cent) completed the questionnaires at 5 years. Among these, 79 (56·0 per cent) had co-morbidities. Patients with co-morbidity had clinically relevant (MD at least 10) and statistically significantly poorer global quality of life (MD −10, 95 per cent confidence interval −12 to −7), and more problems with dyspnoea (MD 10, 6 to 13) throughout the whole follow-up period than those without co-morbidity. Patients with co-morbidity had a clinically relevant worse level of fatigue at 6 months (MD 10, 1 to 19) and 5 years (14, 4 to 24). With regard to specific co-morbidities, only patients with diabetes reported more clinically relevant, but not statistically significant, problems with fatigue at 6 months (MD 16, 2 to 31) and 5 years (MD 13, –5 to 31) compared with patients without co-morbidity. Conclusion: Among survivors of oesophageal cancer surgery, the presence of co-morbidity was associated with poor HRQoL over time and increasing symptoms of fatigue. Abstract : Improving information to patients